Effectiveness of Chicken Manure and Foliar Fertilizer in Decreasing Inorganic Fertilizer Use for Cayenne Pepper (Capsicum frutescens L.) Cultivation in Dryland - Jaya, I Komang Damar; Sudirman, Sudirman; Salta, Legina Aldaeska (Journal of Science and Science Education, 2025)
The use of inorganic fertilizers in high doses for chili pepper (Capsicum frutescens L.) cultivation can negatively impact plant productivity over time. This study aimed to evaluate the effectiveness of chicken manure (CM) and foliar fertilizer (FF) in reducing the reliance on inorganic fertilizers for chili pepper plants grown in dryland conditions. The experiment was conducted in Gumantar Village, North Lombok Regency, from March to August 2023. As the control, an inorganic fertilizer treatment with NPK (16-16-16) at a dose of 1,200 kg/ha was used. The tested treatments included 85% NPK + CM, 70% NPK + CM, 55% NPK + CM, 85% NPK + CM + FF, 70% NPK + CM + FF, and 55% NPK + CM + FF. The dose of chicken manure applied was 20 tons/ha. These treatments were arranged using a randomized block design with three replications. The results indicated that CM, with or without FF, could increase the percentage of flowers that developed into fruits. There were no significant differences in the growth and yield of chili plants among the various treatments, suggesting that CM, with or without FF, could effectively replace up to 45% of the inorganic fertilizers used. This finding indicates that the dependence on inorganic fertilizers in chili pepper cultivation in drylands can be gradually reduced by incorporating organic and foliar fertilizers